Structural and physicochemical properties of rice starch from a variety with high resistant starch and low amylose content - Gu, Xue; Wang, Peng; Huang, Juyuan; Chen, Shuangqin; Li, Dandan; Pu, Shihuang; Li, Juan; Wen, Jiancheng (Frontiers in Nutrition, 2024)
Research on the physicochemical properties of rice-derived endo-sperm high resistant starch (RS) with low amylose content (AC) is limited. In this study, we evaluated the physicochemical characteristics of such a starch variety and revealed that the starch granules exhibit a smoother, more refined surface with distinct edges, increased compactness, higher order of surface, and fewer cavities compared to those of a low RS rice variety. The starch crystal was classified as an A-type, which may be connected to the high amylose-lipid complex content. The branched internal long chains (B2+B3) were abundant, allowing for easy entanglement with other molecular chains and a compact structure. Differential scanning calorimetry revealed the need for high temperature and energy to disrupt the double helix structure within the crystallization region of starch. Furthermore, starch viscosity analysis revealed a high cold paste viscosity, consistency, and setback value, with recrystallization yielding a stable structure, increased viscosity, and enhanced hydrolysis resistance to enzymes.